High relative air humidity influences mineral accumulation and growth in iron deficient soybean plants - Roriz, Mariana; Carvalho, Susana M. P.; Vasconcelos, Marta W. (Frontiers in Plant Science, 2014)
Iron (Fe) deficiency chlorosis (IDC) in soybean results in severe yield losses. Cultivar selection is the most commonly used strategy to avoid IDC but there is a clear interaction between genotype and the environment; therefore, the search for quick and reliable tools to control this nutrient deficiency is essential. Several studies showed that relative humidty (RH) may influence the long distance transport of mineral elements and the nutrient status of plants. Thus, we decided to analyze the response of an ‘Fe-efficient’ (EF) and an ‘Fe-inefficient’ (INF) soybean accession grown under Fe-sufficient and deficient conditions under low (60%) and high (90%) RH, evaluating morphological and physiological parameters. Furthermore, the mineral content of different plant organs was analyzed. Our results showed beneficial effects of high RH in alleviating IDC symptoms as seen by increased SPAD values, higher plant dry weight, increased plant height, root length and leaf area. This positive effect of RH in reducing IDC symptoms was more pronounced in the EF accession. Also, Fe content in the different plant organs of the EF accession grown under deficient conditions increased with RH. The lower partitioning of Fe to roots and stems of the EF accessions relative to dry matter also supported our hypothesis, suggesting a greater capacity of this accession in Fe translocation to the aerial parts under Fe deficient conditions, when grown under high RH.